A structural-cognitive semiotic analysis of the Qur'anic story "Joseph and his Brothers" - Hassanein, Hamada (Public Journal of Semiotics, 2013)
Previous work on the semiotics of Qur'anic narration is fairly sparse (cf. Hassanein, 2009b). In this paper I try to provide a semiotic analysis of the Qur'anic story Joseph and his Brothers, employing a model developed by Grambye and Sonne (2003a). The model draws heavily on the theories of structural-cognitive semiotics (Greimas, 1983; Brandt, 2004) and narratological terminology (Prince, 2003) and illustratively analyses the story's descriptive, narrative and argumentative propositional content, as well as enunciation, and discourse. The three facets of propositional content are examined in light of 3-D, transport, and thematic models, respectively. Enunciation and discourse are tested against enunciative and discursive models, respectively. The application of the general model offers a rich and insightful analysis of the story's text in a religious context, with particular focus placed on enunciation to serve a religious purpose. I find the model efficient in analysing narratives in a genre other than the folktale for which it was developed and I am thus recommending testing it against other narrative texts to figure out what it can further reveal.